Crystal structure of bile salt hydrolase from Lactobacillus salivarius. Issue 5 (1st May 2016) - Xu, Fuzhou; Guo, Fangfang; Hu, Xiao-Jian; Lin, Jun
Abstract : Bile salt hydrolase is an enzyme that is produced by various commensal bacteria in the intestine and is also a key mechanistic microbiome target for enhanced animal and human health. Abstract : Bile salt hydrolase (BSH) is a gut‐bacterial enzyme that negatively influences host fat digestion and energy harvesting. The BSH enzyme activity functions as a gateway reaction in the small intestine by the deconjugation of glycine‐conjugated or taurine‐conjugated bile acids. Extensive gut‐microbiota studies have suggested that BSH is a key mechanistic microbiome target for the development of novel non‐antibiotic food additives to improve animal feed production and for the design of new measures to control obesity in humans. However, research on BSH is still in its infancy, particularly in terms of the structural basis of BSH function, which has hampered the development of BSH‐based strategies for improving human and animal health. As an initial step towards the structure–function analysis of BSH, C‐terminally His‐tagged BSH from Lactobacillus salivarius NRRL B‐30514 was crystallized in this study. The 1.90 Å resolution crystal structure of L. salivarius BSH was determined by molecular replacement using the structure of Clostridium perfringens BSH as a starting model. It revealed this BSH to be a member of the N‐terminal nucleophile hydrolase superfamily. Crystals of apo BSH belonged to space group P 21 21 2, with unit‐cell parameters a = 90.79, b = 87.35, c = 86.76 Å (PDB entry 5hke ). Two BSH molecules packed perfectly as a dimer in one asymmetric unit. Comparative structural analysis of L. salivarius BSH also identified potential residues that contribute to catalysis and substrate specificity.